Genome-Wide Identification and Low-Temperature Expression Analysis of bHLH Genes in Prunus mume - Ding, Aiqin; Ding, Anqi; Li, Ping; Wang, Jia; Cheng, Tangren; Bao, Fei; Zhang, Qixiang (Frontiers in Genetics, 2021)
Prunus mume is an illustrious ornamental woody plant with colorful flowers, delicate fragrances, and graceful tree forms. Low temperature limits its geographical distribution. The basic helix-loop-helix (bHLH) proteins exist in most eukaryotes as a transcription factor superfamily, which play a crucial role in metabolism, physiology, development, and response to various stresses of higher organisms. However, the characteristics of the bHLH gene family and low-temperature response remain unknown in P. mume. In the present study, we distinguished 95 PmbHLH genes in the P. mume whole-genome and analyzed their features. PmbHLHs were divided into 23 subfamilies and one orphan by phylogenetic analysis. Similar gene structures and conserved motifs appeared in the same subfamily. These genes were situated in eight chromosomes and scaffolds. Gene duplication events performed a close relationship to P. mume, P. persica, and P. avium. Tandem duplications probably promoted the expansion of PmbHLHs. According to predicted binding activities, the PmbHLHs were defined as the Non-DNA-binding proteins and DNA-binding proteins. Furthermore, PmbHLHs exhibited tissue-specific and low-temperature induced expression patterns. By analyzing transcriptome data, 10 PmbHLHs which are responsive to low-temperature stress were selected. The qRT-PCR results showed that the ten PmbHLH genes could respond to low-temperature stress at different degrees. There were differences in multiple variations among different varieties. This study provides a basis to research the evolution and low-temperature tolerance of PmbHLHs, and might enhance breeding programs of P. mume by improving low-temperature tolerance.